Metropolitan and city-regional politics in the urban age: why does "(smart) devolution" matter? - Calzada, I (Palgrave Macmillan, 2017)
In recent years, two apparently contradictory but, in fact, complementary socio-political phenomena have been reinforcing each other in the European urban realm: the re-scaling of nation-states through “devolution” and the emergence of two opposed versions of “nationalism” (i.e., the ethnic, non-metropolitanised, state-centric, exclusive, and right-wing populist nationalism and the civic, metropolitanised, stateless, inclusive and progressivist-emancipatory-social democratic nationalism). In light of these intertwined phenomena, this paper suggests how an ongoing, pervasive, and uneven “metropolitanisation effect” is increasingly shaping city-regional political responses by overlapping metropolitan, city-regional, and national political scales and agendas. This effect is clear in three European cases driven by “civic nationalism” that are altering their referential nation-states’ uniformity through “devolution”. This paper will compare three metropolitan (and city-regional) cases in the UK and in Spain, namely, Glasgow (Scotland), Barcelona (Catalonia), and Bilbao (Basque Country), by benchmarking their policy implementation and the tensions produced in reference to their nation-states. This study carried out fieldwork research from January 2015 to June 2017 through several in-depth interviews with stakeholders in the three locations. Despite the so-called pluri-national and federal dilemmas, this paper contributes to examining the side effects of “metropolitanisation” by considering three arguments: one based on geo-economics (“prosperous competitiveness”), one based on geo-politics (“smart devolution”), and one based on geo-democratics (“right to decide”). Finally, adding to the existing research on metropolitan and city-regional politics, this paper demonstrates why “devolution” matters and why it must be taken into serious consideration, as the “metropolitanisation effect” will be key to understanding and transforming the current configurations of nation-states, such as the UK and Spain—as we currently know them—even beyond internal discord around pluri-nationality and quasi-federalism. Ultimately, this paper concludes by suggesting the term “smart devolution” to promote more imaginative and entrepreneurial approaches to metropolitan and city-regional politics, policies, and experimental democracy within these nation-states. By doing so, we can identify and pursue “smart” avenues of timely, subtle, and innovative political strategies for change in the ongoing re-scaling devolution processes occurring in the UK and in Spain and in the consequent changes in the prospects for the refoundational momentum embracing the EU.